The evolution of marketing research in the context of digital transformation of society - Diadyk, Tetiana; Dronova, Tetiana; Burdyak, Oleh; Nestor, Vitalii; Voskresenska, Olena (Edelweiss Applied Science and Technology, 2024)
Marketing research’s relevance in digital transformation is paramount for ensuring business process efficiency. The article aims to analyse the impact of new digital tools on marketing research, identify the main advantages of these methods, and develop recommendations for their optimisation. The methodology involves a comprehensive approach, which includes analysing the experience of international companies, assessing the market, and the practice of applying the latest technologies in marketing research. The results revealed that using big data and social media analytics increases the accuracy and efficiency of marketing campaigns. The article highlights the need to adapt digital approaches to market specifics and consumer needs. The study results indicate that the revenues of the marketing research industry significantly influenced global GDP from 2009 to 2022, with the most substantial impact observed in North America and the weakest in Latin America. The practical significance lies in integrating modern technologies into the marketing research process, which requires marketers to have high technological proficiency. The article outlines the role of data privacy, which demands a responsible approach to information from companies. Several recommended measures are provided to improve marketing research, implement personalised strategies, and enhance staff qualifications. The prospects for further research include developing comprehensive programs that enable the effective use of digital technologies in marketing research.